Cell–cell fusion of mesenchymal cells with distinct differentiations triggers genomic and transcriptomic remodelling toward tumour aggressiveness - Delespaul, Lucile (Sci Rep, 2020)
Cell–cell fusion is a physiological process that is hijacked during oncogenesis and promotes tumour evolution. The main known impact of cell fusion is to promote the formation of metastatic hybrid cells following fusion between mobile leucocytes and proliferating tumour cells. We show here that cell fusion between immortalized myoblasts and transformed fibroblasts, through genomic instability and expression of a specific transcriptomic profile, leads to emergence of hybrid cells acquiring dissemination properties. This is associated with acquisition of clonogenic ability by fused cells. In addition, by inheriting parental properties, hybrid tumours were found to mimic the histological characteristics of a specific histotype of sarcomas: undifferentiated pleomorphic sarcomas with incomplete muscular differentiation. This finding suggests that cell fusion, as macroevolution event, favours specific sarcoma development according to the differentiation lineage of parent cells.